English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

3a + 5c=38
7a + 2c=50

2007-03-10 14:44:16 · 4 answers · asked by Michele N 1 in Science & Mathematics Mathematics

4 answers

Multiyplying the first equation by 2, and the second by 5:

6a + 10c = 76
35a + 10c = 250

Subtracting the above equations:

29a = 174
a = 6

Substituting this value in (3a+5c=38)

18+5c = 38
5c=20
c=4

Hence a=6, c=4

2007-03-10 14:50:20 · answer #1 · answered by Shrey G 3 · 1 0

3a + 5c = 38
7a + 2c = 50

Let's using elimination to solve this. Multiply the top equation by 7 and the bottom equation by 3.

21a + 35c = 266
21a + 6c = 150

Subtract equations,

29c = 116

Solve for c.

c = 116/29 = 4

Now that we have c = 4, we can easily get the other value by plugging this into one of the equation.

3a + 5c = 38. c = 4, so
3a + 5(4) = 38
3a + 20 = 38
3a = 18
a = 6

a = 6, c = 4

2007-03-10 22:49:08 · answer #2 · answered by Puggy 7 · 0 0

I) (3a + 5c=38 (-2)
II) (7a + 2c=50 (5)

I) (-6a - 10c= -76
II) (35a + 10c= 250 (5)
29a = 174
a = 174/29
a = 6

3a + 5c=38
3(6) + 5c = 38
5c = 38 - 18
5c = 20
c = 20 : 5
c = 4
Answer: a = 6 and c = 4
<;;>

2007-03-10 23:01:20 · answer #3 · answered by aeiou 7 · 0 0

(3a + 5c = 38) x 2
(7a + 2c = 50) x 5

6a + 10c = 76
35a + 10c = 250

29a = 174
a = 6
c = (50 - 7a)/2
c = (50 - 7(6))/2
c = (50 - 42)/2 = 8/2 = 4

a = 6 and c = 4

2007-03-10 22:50:46 · answer #4 · answered by Newbody 4 · 0 0

fedest.com, questions and answers